2016
DOI: 10.1007/s40263-016-0371-2
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Ketamine in Refractory and Super-Refractory Status Epilepticus: A Retrospective Study

Abstract: ObjectiveThe aim was to describe the safety and efficacy of (S)-ketamine [(S)-KET] in a series of patients with refractory and super-refractory status epilepticus (RSE and SRSE) in a specialized neurological intensive care unit (NICU).MethodsWe retrospectively analyzed the data of patients with RSE and SRSE treated with (S)-KET in the NICU, Salzburg, Austria, from 2011 to 2015. Data collection included demographic features, clinical presentation, diagnosis, electroencephalogram (EEG) data, anticonvulsant treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 42 publications
1
54
0
5
Order By: Relevance
“…There are 26 studies on the use of KET in SE, including 18 single case reports (14 on adults and four on children) and eight case series (five on adults and three on children) available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 26 studies on the use of KET in SE, including 18 single case reports (14 on adults and four on children) and eight case series (five on adults and three on children) available.…”
Section: Resultsmentioning
confidence: 99%
“…One pediatric case series included only one patient with KET; this study was therefore counted as a case report . Six case series were conducted in a single center, and one was a multicenter study . Except for two prospective pediatric studies, all others were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…28 The case studies presented here provide further support for perampanel as a treatment for RSE. 34 A review of all published studies of ketamine treatment for SE found that 153 (73.9%) adult patients were responders. 33 Inaretrospectivestudy of (S)-ketamine treatment for RSE and SRSE, after a median of three failed AEDs, (S)-ketamine was the final drug administered before SEcessationin27(64.3%)patients;however,four(14.8%)ofthese were also receiving propofol concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…33 Inaretrospectivestudy of (S)-ketamine treatment for RSE and SRSE, after a median of three failed AEDs, (S)-ketamine was the final drug administered before SEcessationin27(64.3%)patients;however,four(14.8%)ofthese were also receiving propofol concurrently. 34 A review of all published studies of ketamine treatment for SE found that 153 (73.9%) adult patients were responders. 33 InareportoffivepatientswithSRSE, stiripentol treatment after failure of 5-8 AEDs was followed by SE cessationinthree(60.0%)patientswithin4daysofadministration.…”
Section: Previous Studies Have Described Varied Outcomes With Othermentioning
confidence: 99%
“…Nevertheless, the high response rate in this study among patients with SRSE not previously responding to other treatments stands in comparison to previous observational studies. In a retrospective study of 42 patients with RSE and SRSE, (s)‐ketamine infusion for a median of 3 days resulted in a survival rate of 54.8% and resolution of SRSE in 64% of patients 48. Another retrospective case series demonstrated a 57% control rate and 57% survival rate when ketamine was administered in 58 subjects with 60 episodes, although no subject responded when ketamine was introduced 8 days beyond status epilepticus onset, compared to a large proportion of patients in our cohort responding after a 9.2‐day mean duration of status epilepticus before brexanolone administration 49.…”
Section: Discussionmentioning
confidence: 99%